Uffe Hansen: Grundtvigs salmedigtning. Dens historie og indhold. III. 1851-1872 - Kjær, Kristian (Grundtvig-studier, 1968)
Uffe Hansen, Grundtvigs Salmedigtning. Dens Historie og Indhold. I l l Reviewed by Kristian Kjær.The third and last volume of Uffe Hansen’s work deals with the hymns and songs of Grundtvig’s Sang-Værk which belong to the period from 1851 to 1872. The book contains a paraphrase of the poems with illustration of such passages as may give rise to difficulties of comprehension, either because of their concentrated form or because of Grundtvig’s personal style. The chief emphasis is laid upon the contents of the poetry. This applies to Uffe Hansen’s treatment of the individual poem as well as to his arrangement of the whole book. Nearly all the poems are arranged in two main groups according as they may be said to express an ethic or should be characterized as dogmatic. Within these groups the poems are divided into subgroups according to theme.